Contribution of Availability and Needs to Price Stability of Shallot Products (Early Cases of the Covid-19 Pandemic in Semarang) - Karnowahadi Karnowahadi; Endang Sulistyani; Dody Setyadi; Clarissa Putri Kharisma (UNEJ e-Proceeding, 2021)
This study aims to analyze the effect of Availability and Needs on the Shallot Price Stability in the Kota Semarang. This study uses secondary data that is already available at Dinas Perdagangan Kota Semarang. The data used is the daily data on shallot commodities in April and May 2020 which consists of data on Availability, Needs, and Price Stability obtained from the Dinas Perdagangan Kota Semarang. The data were tested for classical assumptions. The statistical analysis tool used is multiple linear regression analysis. The coefficient of determination in this study is 0.596, which means that the contribution of Availability and Needs to the Price Stability of shallots is 59.6% and the remaining 40.4% is influenced by other variables not examined in this study. The results showed that the availability and demand for shallots had an effect on price stability. Keywords: Shallot, Price Stability, Availability, Needs